Pengaruh Adaptabilitas Karier, Efikasi Diri, Disiplin Diri, Dan Literasi Digital Terhadap Minat Berwirausaha Siswa/I SMK - Anggana, Syeh Umar; Sutadji, Eddy; Tuwoso, Tuwoso (Universitas Nahdlatul Ulama Blitar, 2025)
Presidential Regulation (PERPRES) Number 2 of 2022 concerning National Entrepreneurship Development for 2021-2024, mandates that the target entrepreneurship ratio in 2024 is 4.0%. Vocational education that oversees SMK encourages students to be productive, one of which is through entrepreneurship. Entrepreneurial interest is one of the important precursor variables for entrepreneurship. This study uses a quantitative approach survey method. The form of problem formulation used in this study is associative-causal. The sample used in this study amounted to 222 students from public vocational schools in Malang City. The data collection technique used was a questionnaire. Data analysis techniques used include descriptive, partial correlation, and multiple regression. The conclusion in this study shows that career adaptability and self-discipline have no partial effect on students' entrepreneurial interest, while self-efficacy and digital literacy have a partial effect on students' entrepreneurial interest. The results also reveal that there is no simultaneous influence between career adaptability, self-efficacy, self-discipline, digital literacy on entrepreneurial interest of vocational students in Malang City.